Investigating the Dimensions of Student Voice in Co-Constructed Assessment Tasks - Karkhaneh, Yasna (Assessment and Practice in Educational Sciences, 2023)
This study aims to explore the dimensions of student voice as expressed and experienced in the context of co-constructed assessment tasks in secondary educational settings. Using a qualitative research design, this study involved semi-structured interviews with 20 participants (students and teachers) from secondary schools in Tehran. Participants were selected through purposive sampling based on their involvement in classrooms where assessment tasks were co-designed or collaboratively modified. Data collection continued until theoretical saturation was reached. All interviews were transcribed verbatim and analyzed thematically using NVivo software. Open, axial, and selective coding methods were applied to identify recurring patterns and to develop a framework representing the conceptual dimensions of student voice in co-constructed assessment practices. Thematic analysis yielded three overarching categories: (1) Participation and Agency, which encompassed student decision-making, preference expression, and autonomy in assessment processes; (2) Pedagogical Relationships and Support, which highlighted the importance of trust, teacher responsiveness, and guided scaffolding of student voice; and (3) Impact on Learning and Assessment Practice, which included increased engagement, enhanced assessment literacy, and a cultural shift toward collaborative and reflective assessment environments. Participants reported that co-construction enhanced their motivation, confidence, and metacognitive awareness, though some noted persistent hesitations and unequal participation across student groups. The findings demonstrate that co-constructed assessment tasks provide fertile ground for activating meaningful student voice, particularly when supported by relational pedagogy and inclusive classroom cultures. Integrating student voice into assessment design promotes deeper learning, shared responsibility, and a more democratic approach to evaluation. However, effective implementation requires intentional scaffolding, cultural sensitivity, and ongoing teacher professional development.